2017
DOI: 10.1111/1759-7714.12576
|View full text |Cite
|
Sign up to set email alerts
|

Pathological diagnosis of pulmonary large cell neuroendocrine carcinoma by endobronchial ultrasound‐guided transbronchial needle aspiration

Abstract: BackgroundPulmonary large cell neuroendocrine carcinoma (LCNEC) is a relatively rare subtype of lung malignancy. According to revised 2015 World Health Organization (WHO) criteria for the pathological diagnosis of LCNEC, neuroendocrine markers must be examined by immunohistochemistry. In this study, we reevaluated endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) samples of patients previously diagnosed with LCNEC using the revised WHO criteria.MethodsClinical tissue samples that had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Previous studies that aimed to evaluate the LCNEC WHO 2015 criteria on biopsy specimens have shown high diagnostic specificity . Similarly, we provide evidence that the specificity for LCNEC on a biopsy specimen is acceptable (i.e.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Previous studies that aimed to evaluate the LCNEC WHO 2015 criteria on biopsy specimens have shown high diagnostic specificity . Similarly, we provide evidence that the specificity for LCNEC on a biopsy specimen is acceptable (i.e.…”
Section: Discussionsupporting
confidence: 68%
“…H&E slides of both resection and biopsy specimens were examined for (i) cell type, presence of cytoplasm and tumour to lymphocyte ratio to assess NSCLC of SCLC features according to the WHO 2015 classification, (ii) the presence of neuroendocrine morphology, (iii) estimated mitotic activity in non-crushed fields [≤10, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] or >30 mitoses/10 high-power field (HPF)], (iv) necrosis [none, 'dot-like' (=as occasionally seen in atypical carcinoids) or abundant (= more extensive than 'dot-like')]. If available, the MIB1 (Ki-67) staining was scored into <25% and >25%.…”
Section: P a N E L C O N S E N S U S P A T H O L O G Y R E V I S I O Nmentioning
confidence: 99%
See 2 more Smart Citations
“…Limited fine needle aspirate tissue especially from lung lesion is often not able to confirm the diagnosis. Despite the preference for larger samples endobronchial ultrasound-guided transbronchial needle aspiration has been shown to be effective in diagnosis of LCNEC (70). For pulmonary and gastrointestinal primary sites cross sectional imaging should be done for staging including CT of the chest, abdomen, and pelvis with intravenous contrast.…”
Section: Diagnosismentioning
confidence: 99%